2018
DOI: 10.1371/journal.pone.0193108
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish Neonatal Jaundice Online Registry: A national root cause analysis

Abstract: BackgroundNeonatal jaundice (NNJ) is common, but few root cause analyses based on national quality registries have been performed. An online registry was established to estimate the incidence of NNJ in Turkey and to facilitate a root cause analysis of NNJ and its complications.MethodsA multicenter prospective study was conducted on otherwise healthy newborns born at ≥35 weeks of gestation and hospitalized for only NNJ in 50 collaborator neonatal intensive care units across Turkey over a 1-year period. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
2
31
2
3
Order By: Relevance
“…Besides, a male has a higher concentration of bilirubin and hige risk of acute bilirubin encephalopathy as compared with females. 12 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, a male has a higher concentration of bilirubin and hige risk of acute bilirubin encephalopathy as compared with females. 12 35 …”
Section: Discussionmentioning
confidence: 99%
“…7 11 12 Hyperbilirubinaemia can be described in the form of pathological, physiological, jaundice secondary to breast milk or breastfeeding failure, and haemolytic jaundice due to glucose-6-phosphate dehydrogenase deficiency, ABO and Rh incompatibility. [12][13][14] Jaundice can be severe when it is seen anywhere on the body on the first day or the What is known about the subject?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model expected no severe hyperbilirubinemia due to Rh disease in HIC [24]. The Turkish Neonatal Registry reported the frequency of Rh disease as 5.4 % of all admissions due to hyperbilirubinemia [16]. Rh isoimmunization constituted 11.3% of all severe hyperbilirubinemia cases in our study population but its frequency increased to about 18% among infants receiving exchange transfusion and developing ABE.…”
Section: Discussionmentioning
confidence: 56%
“…Erdeve etal conducted a nationwide root cause analysis of NJ in Turkey and found several noteworthy observations, such as the two most common risk factors for NJ were a haemolytic aetiology followed by lack of initiation of proper breastfeeding, and recommended blood type screening and adequate follow-up during the first week of life to national healthcare system. 3 A meta-analysis on risk factors for severe neonatal hyperbilirubinaemia in LMICs also showed that infants at risk of severe hyperbilirubinaemia in LMICs are associated with maternal and neonatal factors that can be effectively addressed by available interventions to curtail the disease burden prevailing in the affected countries. 5 …”
mentioning
confidence: 99%